2020
DOI: 10.1101/2020.01.13.905588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotten-skin disease significantly changed giant spiny frog(Paa spinosa) gut microbiota

Abstract: The composition and abundance of gut microbiota is essential for host health 22 and immunity. Gut microbiota is symbiotic with the host, so changes in the host diet, 23 development, and health will lead to changes in the gut microbiota. Conversely, changes 24 in the gut microbiota also affect the host conditions. In this experiment, 16S rRNA high-25 throughput sequencing was used to compare the gut microbiota composition of 5 26 healthy Paa Spinosa and 6 P. spinosa with rotten-skin disease. Results: the gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Research on Asiatic toads ( Bufo gargarizans ) has revealed considerable structural differences between the large and small intestines [ 26 ]. Moreover, rotten-skin disease is shown to significantly alter the gut microbiota of the giant spiny frog ( Paa spinosa ) [ 27 ]. As a variable temperature vertebrate, the larvae (tadpoles) of frogs live in water, while the majority of adults live on land.…”
Section: Introductionmentioning
confidence: 99%
“…Research on Asiatic toads ( Bufo gargarizans ) has revealed considerable structural differences between the large and small intestines [ 26 ]. Moreover, rotten-skin disease is shown to significantly alter the gut microbiota of the giant spiny frog ( Paa spinosa ) [ 27 ]. As a variable temperature vertebrate, the larvae (tadpoles) of frogs live in water, while the majority of adults live on land.…”
Section: Introductionmentioning
confidence: 99%